2016
DOI: 10.37212/jcnos.334114
|View full text |Cite
|
Sign up to set email alerts
|

Is Hypericum perforatum agonist or antagonist of TRPC6 in neurons?

Abstract: Journal of Cellular Neuroscience and Oxidative Stress is an online journal that publishes original research articles, reviews and short reviews on the molecular basis of biophysical, physiological and pharmacological processes that regulate cellular function, and the control or alteration of these processes by the action of receptors, neurotransmitters, second messengers, cation, anions, drugs or disease. Areas of particular interest are four topics. They are; A-Ion Channels (Na +-K + Channels, Clchannels, Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Similar to current results, the protective role of HP in rat sciatic nerve injury through inhibition of TRPM2 channels was reported (Uslusoy et al, 2017). Recently, it was reported that cutaneous wound healing is accelerated by mechanical stress, and treatment with hyperforin enhanced the acceleration through the facilitation of TRPC6 Ca 2+ signaling in HaCaT human keratinocyte cells and neurons (Nazıroğlu, 2016;Takada et al, 2017). More recently, the involvement of 2-APB through inhibition of TRPV2 on hypertrophic scar formation and wound healing in cell culture of rat keratinocytes was also reported (Ishii et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to current results, the protective role of HP in rat sciatic nerve injury through inhibition of TRPM2 channels was reported (Uslusoy et al, 2017). Recently, it was reported that cutaneous wound healing is accelerated by mechanical stress, and treatment with hyperforin enhanced the acceleration through the facilitation of TRPC6 Ca 2+ signaling in HaCaT human keratinocyte cells and neurons (Nazıroğlu, 2016;Takada et al, 2017). More recently, the involvement of 2-APB through inhibition of TRPV2 on hypertrophic scar formation and wound healing in cell culture of rat keratinocytes was also reported (Ishii et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…The 'St. John's wort' Hypericum perforatum is a wellknown traditional plant, and it has been used in the treatment of several diseases such as depression, inflammatory, and skin diseases (Meinke et al, 2012;Nazıroğlu, 2016). The main components of H. perforatum are hyperforin, flavonoids, hypericin, and their anti-apoptosis and antioxidant properties through inhibition of TRPM2 channel were reported in neuropathic pain, neutrophil activation and mechanical brain injury (Nazıroğlu et al, 2014a(Nazıroğlu et al, , 2014b(Nazıroğlu et al, , 2014cUslusoy et al, 2017).…”
Section: Introductionmentioning
confidence: 99%